Underestimated increase and intensification of humid-heat extremes across southeast China due to humidity data inhomogeneity - Li, Xuezhu; Chen, Yang; Zhu, Yani; Shi, Yan; An, Ning; Liao, Zhen (Frontiers in Environmental Science, 2023)
When co-occurring with elevated levels of ambient relative humidity (RH), hot extremes are more perceivable and consequently more health-damaging. Quantifying changes in humid-heat extremes has therefore gained considerable scientific and societal attention, but a fundamental yet critical aspect to the estimation—data reliability—has been largely downplayed in previous analysis. By comparing ~10 observational and reanalysis datasets to fully-homogenized observations across China, we report ubiquitous inhomogeneity in RH series in these popularly-used datasets (including HadISD(H) and ERA5), which accordingly produce unrealistically strong drying trends 2~3 times the homogenized dataset-based estimate during 1979—2013 in warm-moist southeast China. Locally, an inhomogeneity-caused exaggeration of drying by a magnitude of 1% decade-1 translates into a significant underestimation of increasing rates for frequency and intensity of humid-heat extremes by more than 1.2 days decade-1 and 0.07% decade-1 respectively. From a regional perspective, these inhomogeneous records have underestimated the frequency increase of extremes by up to 2 days decade-1 and their intensification by up to 0.4°C decade-1 in southeast China. Extremes identified via homogenized and non-homogenized datasets also differ in the bivariate joint distribution structure, with former cases featuring similarly hot temperatures yet discernably lower humidity.